Socio-economic Sustainability in Poland. SEM Analysis at Regional Level - Michal Bernard Pietrzak; Adam P. Balcerzak (Institute of Economic Research (IER), 2016)
Improving conditions for sustainable development has been a major aim of every Polish government since the beginning of transformation process. Thus, the aim of the paper is to analyse the level of sustainable development in Poland at re-gional level. The research was conducted at NUTS 3 level for the years 2010-2013. The analysis was based on the data from Central Statistical Office of Poland. It was assumed that the phenomenon of socio-economic sustainability at regional level should be considered as a multivariate latent variable. As a result, it was measured with application of Structural Equation Modeling (SEM). The proposed model was based on eight observable variables that are often pointed in the literature as measures of socio-economic development and human welfare. Application of SEM model allowed to verify the usefulness of the observable variables for analysis of the phenomenon of sustainable development in Poland at regional level. The conducted research confirmed serious disparities at regional level in the sphere of socio-economic sustainability that must be the subject of special interest and counteractions of Polish government.
Keywords: Q01; C38; 330; Structural Equation Modeling (SEM); regional analysis; sustainable de-velopment; Poland